Review of Fischer, Johan and Jammes, Jérémy (Eds.). Muslim Piety As Economy: Markets, Meaning and Morality in Southeast Asia - Althubaiti, Haytham (International Journal of Management and Business Economics, 2024)
This book review provides an overview and analysis of a comprehensive examination of Muslim piety and its intersection with the economy in Southeast Asia, specifically focusing on Brunei, Indonesia, and Malaysia. In eleven chapters, contributors from various disciplines including anthropology, politics, history, religious studies, economy, and business offer diverse perspectives on the construction of Muslim piety between Islam and the economy, arguing that Southeast Asian Muslim identities are deeply intertwined with both nationality and religion. Key themes explored include the role of Islamic discourses in addressing corruption, the evolution of Islamic economy during colonial times, the significance of halal certification in Brunei’s economy, advancements in science contributing to the halal industry, and the exploration of modesty in Islamic fashion. Through extensive fieldwork and analysis, the book sheds light on the complexities of navigating the halal industry within Southeast Asian societies. Overall, it offers valuable insights for scholars and students across various disciplines, including politics, anthropology, sociology, and religious studies, while presenting its findings in a clear and accessible manner.